Being a 'Clydesider' in the age of deindustrialisation: skilled male identity and economic restructuring in the West of Scotland since the 1960s. (3rd March 2020) - Phillips, Jim; Wright, Valerie; Tomlinson, Jim
ABSTRACT: This article examines the relationship between long-running deindustrialisation and skilled male employment culture in the West of Scotland. The age of deindustrialisation is a valuable designation: the contraction of industrial production and employment in the United Kingdom was gradual rather than sudden, managed carefully in the 1960s and 1970s and then recklessly in the 1980s. In Scotland there was an important transition in the 1960s from established to younger industrial sectors. In the sphere of employment culture this tested the Clydesider skilled male identity, which was constructed and reproduced in workplaces and industrial communities. The resilience of this identity is tracked through oral history examination of workers employed at the Fairfields shipyard in Govan, Glasgow, and the Linwood car plant, ten miles west in Renfrewshire. The Clydesider identity was derived from shipyard employment culture. It privileged earnings, workplace voice and relative autonomy from managerial supervision. Workers at Linwood used the Clydesider identity to advance their influence on the shop floor, contesting the frustrations of assembly goods manufacturing and asserting skill and autonomy. The article shows how manual workers on the Clyde adjusted to and made sense of deindustrialisation in the 1960s and 1970s in moral economy terms. The protracted and incomplete 'half-life' of deindustrialisation contained positive as well as negative effects.